Uncovering the Exosomes Diversity: A Window of Opportunity for Tumor Progression Monitoring - Maisano, Domenico (Pharmaceuticals (Basel), 2020)
Cells can communicate through special “messages in the bottle”, which are recorded in the bloodstream inside vesicles, namely exosomes. The exosomes are nanovesicles of 30–100 nm in diameter that carry functionally active biological material, such as proteins, messanger RNA (mRNAs), and micro RNA (miRNAs). Therefore, they are able to transfer specific signals from a parental cell of origin to the surrounding cells in the microenvironment and to distant organs through the circulatory and lymphatic stream. More and more interest is rising for the pathological role of exosomes produced by cancer cells and for their potential use in tumor monitoring and patient follow up. In particular, the exosomes could be an appropriate index of proliferation and cancer cell communication for monitoring the minimal residual disease, which cannot be easily detectable by common diagnostic and monitoring techniques. The lack of unequivocal markers for tumor-derived exosomes calls for new strategies for exosomes profile characterization aimed at the adoption of exosomes as an official tumor biomarker for tumor progression monitoring.